A dispersing aid for lithium-ion battery slurry and its application
The dispersion additive made by the polymerization of polypropylene glycol and polyethylene glycol solves the problems of poor viscous and fluidity of lithium battery slurry, improves the dispersion effect and battery performance of electrode active substances, and reduces resistance and alternating current Internal resistance.
Patent Information
- Application Number
- CN202210915803.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-01
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-08-01
AI Technical Summary
The viscosity and poor fluidity of lithium battery paste lead to poor electrode coating effect, affecting the electrode sheet resistance and battery capacity.
Using dispersion aids made of polypropylene glycol, polyethylene glycol and specific alcohols or phenol polymerization, polyether segments are formed through condensation and dehydration reaction, providing hydrophilic and lipophilic groups, reducing surface tension of solid-liquid interfaces, and improving slurry Material flowability and solids content.
On the premise of ensuring conductive properties, the risk of secondary aggregation of particles is reduced, the uniform dispersion of electrode active substances is improved, the battery AC internal resistance is reduced, and the battery capacity and coating convenience are improved.
Smart Images

Figure BDA0003775554800000051 
Figure BDA0003775554800000061 
Figure BDA0003775554800000071
Abstract
Description
Technical Field
[0001] The invention relates to a dispersing aid for lithium ion battery slurry, in particular to a neutral dispersing aid which can be applied to both positive electrode slurry and negative electrode slurry, and belongs to the technical field of lithium batteries. Background Art
[0002] Lithium-ion batteries are widely used as power sources for various mobile devices due to their advantages such as high energy density, high operating voltage, wide application temperature range and long cycle life. They are even gradually replacing other traditional batteries in the fields of aviation, aerospace, navigation, automobiles, medical equipment, etc. In particular, their high energy density has made an important contribution to the miniaturization of mobile devices.
[0003] Lithium-ion batteries are composed of a positive electrode, a negative electrode, a separator and an electrolyte. Taking lithium iron phosphate batteries as an example, the reaction that occurs during charging is: LiFePO4→Li-xFePO4+xLi+x e- , the reaction that occurs during discharge: Li-xFePO4+xLi++x e- →LiFePO4, in short, the working principle of lithium-ion batteries is the flow of electrons between the positive and negative electrodes.
[0004] When lithium-ion batteries are formed, the positive electrode slurry and the negative electrode slurry need to be coated on aluminum foil to make the positive electrode and the negative electrode respectively. Therefore, the characteristics of the slurry are directly related to the coating quality of the electrode. Due to the increasingly high requirements for the capacity of lithium batteries, it is usually achieved by increasing the proportion of electrode active substances in the slurry. This will result in a high solid content in the slurry, which is viscous and has poor fluidity, thereby affecting the coating effect of the electrode and further affecting the efficiency of the lithium battery preparation process.
[0005] In response to this situation, practitioners in this field have conducted extensive research. Existing public reports have disclosed some dispersants specifically for lithium battery slurries, such as polyvinyl pyrrolidone, phosphites, Triton-X, etc. The main disadvantage of this type of dispersant is that there is a risk of decomposition and gas production, which affects the safety of the battery cells; secondly, traditional dispersants and dispersants with a single functional group are not effective enough in solving the viscosity and gel problems of lithium battery slurries. Summary of the invention
[0006] The present invention aims to solve the problem that the slurry for lithium batteries has poor viscosity and fluidity, which affects the electrode coating effect and further leads to increased electrode sheet resistance and reduced gram capacity, and provides a dispersing aid for lithium ion battery slurry and its application.
[0007] The technical solution of the present invention to solve the above technical problems is as follows:
[0008] A dispersing aid for lithium-ion battery slurry, the structural formula of which is as follows:
[0009] RO-(CH2CH2O) n (CH2CH2CH2O) m H, wherein R represents C2-C8 alkyl, C2-C8 alkenyl, 4-(C4-C10 alkyl)phenyl or C4-C20 alkylcarbonyl, n is 3-50, and m is 0-50.
[0010] Preferably, R represents C2-C8 alkyl, C2-C8 alkenyl, 4-(C4-C8 alkyl)phenyl or C8-C16 alkylcarbonyl, n is 10-30, and m is 10-40.
[0011] Further preferably, R represents C3-C6 alkyl, C3-C6 alkenyl, 4-(C4-C8 alkyl)phenyl or C8-C16 alkylcarbonyl, n is 15-25, and m is 20-30.
[0012] The alkyl and alkenyl groups described in the present invention may be linear or branched, for example, the alkyl group may be, for example, C1 alkyl-methyl; C2 alkyl-ethyl; C3 alkyl-propyl, such as n-propyl or isopropyl; C4 alkyl-butyl, such as n-butyl, isobutyl, tert-butyl or 2-butyl; C5 alkyl-pentyl, such as n-pentyl, isopentyl; C6 alkyl-hexyl, such as n-hexyl, isohexyl and 1,3-dimethylbutyl. Similarly, the alkenyl group may be, for example, vinyl, allyl, 1-methylprop-2-ene-1-yl, 2-methylprop-2-ene-1-yl, but-2-ene-1-yl, but-3-ene-1-yl, 1-methylbut-3-ene-1-yl and 1-methylbut-2-ene-1-yl.
[0013] The dispersing aid of the present invention is polymerized from polypropylene glycol, polyethylene glycol and an alcohol, acid or phenol corresponding to R, and can be obtained by referring to the following reaction process:
[0014] ROH+HO-(CH2CH2O) n -H→RO-(CH2CH2O) n -H (1)
[0015] OH-(CH2CH2CH2O) m -H+CH3COOH→CH3COO-(CH2CH2CH2O) m -H (2)
[0016] RO-(CH2CH2O) n -H+CH3COO-(CH2CH2CH2O) m -H→RO-(CH2CH2O) n (CH2CH2CH2O) m H+CH3COOH (3)
[0017] (1) Polyethylene glycol and ROH undergo condensation dehydration reaction under the catalysis of concentrated sulfuric acid and in the presence of an organic solvent at 30-35° C. under stirring conditions, wherein the molar ratio of polyethylene glycol to ROH is (0.6-0.8):1, to generate polyethylene glycol monoether;
[0018] (2) polypropylene glycol and acetic acid react with concentrated sulfuric acid as catalyst and in the presence of an organic solvent at 25-30° C. under stirring conditions, wherein the molar ratio of polypropylene glycol to acetic acid is 1:(1.1-1.2), thereby generating carboxyl-terminated polypropylene glycol;
[0019] (3) Polyethylene glycol monoether and carboxyl-terminated polypropylene glycol are reacted in a dry container with tetrahydrofuran as solvent in the presence of a condensation agent in an inert atmosphere at 25-40° C. for 2-3 days with stirring. The molar ratio of polyethylene glycol monoether to carboxyl-terminated polypropylene glycol is 1:1, thereby obtaining RO-(CH2CH2O) n (CH2CH2CH2O) m H.
[0020] The working principle of the dispersing aid for lithium battery slurry claimed in the present invention is as follows:
[0021] The two ends of the polyether segment are respectively a hydrophilic group and a lipophilic group, which can form an effective steric hindrance in the slurry to prevent the solid particles from settling, thereby reducing the viscosity of the slurry and effectively inhibiting gelation. From the perspective of the microscopic interface, the hydrophilic group and the lipophilic group can effectively reduce the surface tension of the solid-liquid interface, improve the wetting and penetration properties, increase the solid content of the electrode active material and the ease of coating, and are conducive to the uniform dispersion of particles such as electrode active materials and conductive carbon, thereby improving the performance of the battery.
[0022] The beneficial effects of the dispersing aid provided by the present invention are:
[0023] (1) The additive of the present invention is specially designed according to the characteristics of the materials in the lithium battery slurry. It can reduce the risk of secondary aggregation of particles and improve the fluidity of the slurry while ensuring that the conductive performance of the lithium battery is not affected, thereby reducing the resistance of the electrode, increasing the gram capacity of the battery, and reducing the AC internal resistance of the battery;
[0024] (2) The dispersing aid of the present invention is a neutral aid and can be used in both positive electrode slurry and negative electrode slurry, thus having a wider application range.
[0025] (3) The dispersing aid of the present invention is easy to use and does not require a special pulping process. The dispersing aid of the present invention can be added in proportion to the original pulping process to achieve the dispersion and viscosity reduction effect without increasing the process cost.
[0026] The present invention also claims a slurry for lithium-ion batteries, comprising the above-mentioned dispersing aid.
[0027] Preferably, the slurry further comprises an electrode active material and a conductive agent, and the electrode active material is a positive electrode active material or a negative electrode active material.
[0028] Preferably, the positive electrode active material is one or more of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, nickel cobalt manganese ternary material, and nickel cobalt aluminum oxide ternary material; the negative electrode active material is graphite, hard carbon, soft carbon, MCMB (mesophase carbon microbeads), graphene, silicon or lithium titanate, and the conductive agent is one of carbon black or carbon nanotubes or a combination of the two.
[0029] Preferably, when the slurry is applied to the positive electrode, the slurry also contains a binder and an organic solvent, the binder is polyvinylidene fluoride, and the organic solvent is N-methylpyrrolidone. When the slurry is applied to the negative electrode, the slurry also contains a binder, a thickener or water, and the binder is SBR (styrene-butadiene rubber).
[0030] The present invention also claims protection for a pole piece for a lithium-ion battery, the surface of the pole piece being coated with the aforementioned slurry for a lithium-ion battery.
[0031] The present invention also claims protection for a lithium-ion battery, comprising the aforementioned electrode sheet for a lithium-ion battery. DETAILED DESCRIPTION
[0032] The principles and features of the present invention are described below in conjunction with examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.
[0033] The structural formula of the dispersing aid used in the examples is described as follows:
[0034]
[0035] Example 1: Effect of application in positive electrode slurry
[0036] The specific preparation steps of the lithium battery positive electrode slurry of the experimental groups 1-6 and the control group 1 are as follows:
[0037] 1) mixing and stirring the binder and the organic solvent to obtain a glue solution A;
[0038] 2) adding the aforementioned dispersants AF to the above-mentioned glue solution A respectively and stirring evenly to obtain glue solution B;
[0039] 3) Adding the conductive agent to the glue solution B to obtain a conductive agent slurry;
[0040] 4) Adding the positive electrode active material into the conductive agent slurry to obtain a positive electrode slurry.
[0041] The weight ratio of each raw material in the above method is, positive electrode active material: conductive agent: dispersant: binder = 93:3:3:1; wherein the positive electrode active material is lithium iron phosphate produced by Hunan Yuneng New Energy Battery Material Co., Ltd., the conductive agent is a mixture of conductive carbon black and carbon nanotubes in a mass ratio of 1:1, the binder is polyvinylidene fluoride, the organic solvent is N-methylpyrrolidone, and the dispersants used in Examples 1-6 are dispersant A, dispersant B, dispersant C, dispersant D, dispersant E and dispersant F, respectively.
[0042] No dispersant was added to the control group 1, and the other components of the slurry were the same as those of the experimental groups 1-6.
[0043] Take the freshly prepared slurry for testing respectively. After standing for 24 hours, stir the slurry for 1 minute and then test it. Use Lichen ND-10 rotational viscometer and 2# rotor to insert the rotor into the slurry to be tested. The test speed is 100 rpm and the test time is 60 s. The viscosity value of the slurry is obtained by taking the average value of multiple points. The test results are shown in Table 1.
[0044] Table 1 Slurry viscosity and solid content of experimental groups 1-6 and control group 1
[0045]
[0046] It can be seen from the data in Table 1 that after the dispersant of the present invention was added to the experimental groups 1-6, the solid content of the freshly prepared slurry increased by 4-6% relative to the control group 1. After 24 hours, the slurry of the control group 1 gelled, while the slurry of the experimental groups 1-6 still had good fluidity, indicating that the dispersing aid of the present invention has a good dispersing effect on the positive electrode slurry.
[0047] Example 2: Effect of application in negative electrode slurry
[0048] The specific preparation process of the negative electrode slurry of lithium batteries of experimental groups 7-12 and control group 2 is as follows:
[0049] 1) Add the thickener and deionized water into a vacuum mixer, stir for 4-5 hours and then set aside to prepare thickener rubber A;
[0050] 2) Add the conductive agent to the thickener rubber material A, and continue vacuum stirring for 1.5-2.5 hours to obtain rubber material B;
[0051] 3) Add the negative electrode active material and dispersant to the rubber material B, stir in vacuum for 3-4 hours, then add deionized water to adjust the viscosity, and continue stirring for about 1 hour to obtain rubber material C;
[0052] 4) Add a binder to the rubber material C, continue vacuum stirring for 30-45 minutes, and obtain the negative electrode slurry after sieving the material.
[0053] The weight ratio of each raw material is as follows: negative electrode active material: conductive agent: thickener: dispersant: binder = 92:4:1.5:1.5:1; the negative electrode active material is graphite, the conductive agent is a mixture of conductive carbon black and carbon nanotubes in a mass ratio of 1:1, the thickener is sodium carboxymethyl cellulose, the binder is styrene-butadiene rubber, and the dispersants are dispersant A, dispersant B, dispersant C, dispersant D, dispersant E and dispersant F.
[0054] No dispersant was added to the control group 2, and the other components of the slurry were the same as those of the experimental groups 7-12.
[0055] Take the freshly prepared slurry for testing respectively. After standing for 24 hours, stir the slurry for 1 minute and then test it. Use Lichen ND-10 rotational viscometer and 2# rotor to insert the rotor into the slurry to be tested. The test speed is 100 rpm and the test time is 60 s. Use the multi-point average method to obtain the viscosity value of the slurry. The test results are shown in Table 2.
[0056] Table 2 Slurry viscosity and solid content of experimental groups 7-12 and control group 2
[0057]
[0058] It can be seen from the data in Table 2 that after adding the dispersing aid of the present invention to the negative electrode slurry of experimental groups 7-12, compared with the control group 2, the solid content of the freshly prepared slurry is increased by 3-5%, the initial viscosity is slightly improved, and the slurry of the control group 2 gels after 24 hours, while the slurry of the experimental groups 7-12 still has good fluidity, indicating that the dispersing aid of the present invention also has a good dispersing effect on the negative electrode slurry.
[0059] Example 3: Comparative experimental results of positive electrode slurry
[0060] The preparation method of the positive electrode slurry of the lithium battery of the experimental group 13-14 and the control group 3-5 is as follows:
[0061] 1) mixing and stirring the binder and the organic solvent to obtain a glue solution A;
[0062] 2) adding a dispersant to the above-mentioned glue solution A and stirring evenly to obtain glue solution B;
[0063] 3) Adding the conductive agent into the glue solution B to obtain a conductive agent slurry;
[0064] 4) Adding the positive electrode active material into the conductive agent slurry to obtain a positive electrode slurry.
[0065] Among them, the weight ratio of each raw material is, positive electrode active material: conductive agent: dispersant: binder = 92:3.5:3.5:1; the positive electrode active material is lithium iron phosphate produced by Hunan Yuneng New Energy Battery Material Co., Ltd., the conductive agent is a mixture of conductive carbon black and carbon nanotubes in a mass ratio of 1:1, the binder is polyvinylidene fluoride, the organic solvent is N-methylpyrrolidone, the dispersants of experimental groups 13 and 14 are dispersants B and dispersant C respectively, the dispersant of control group 3 is polyvinylpyrrolidone, the dispersant of control group 4 is triethyl phosphite, and the dispersant of control group 5 is Triton X.
[0066] Take the freshly prepared slurry for testing respectively. After standing for 24 hours, stir the slurry for 1 minute and then test it. Use Lichen ND-10 rotational viscometer and 2# rotor to insert the rotor into the slurry to be tested. The test speed is 100 rpm and the test time is 60 s. Use the multi-point average method to obtain the viscosity value of the slurry. The test results are shown in Table 3.
[0067] Table 3 Slurry viscosity and solid content of experimental groups 13-14 and control groups 3-5
[0068]
[0069] It can be seen from the data in Table 3 that compared with other existing dispersants, the solid content of the positive electrode slurry obtained by using the dispersant of the present invention is relatively higher, and the viscosity of the slurry obtained after being placed for 24 hours is significantly reduced, which has a significant effect of improving the fluidity of the slurry.
[0070] Example 4: Comparative experimental results of negative electrode slurry
[0071] The specific preparation process of the negative electrode slurry of lithium batteries of the experimental group 15-16 and the control group 6-8 is as follows:
[0072] 1) Add the thickener and deionized water into a vacuum mixer, stir for 4-5 hours and then set aside to prepare thickener rubber A;
[0073] 2) Add the conductive agent to the thickener rubber material A, and continue vacuum stirring for 1.5-2.5 hours to obtain rubber material B;
[0074] 3) Add the negative electrode active material and dispersant to the rubber material B, stir it in vacuum for 3-4 hours, add deionized water to adjust the viscosity, and continue stirring for about 1 hour to obtain rubber material C;
[0075] 4) Add a binder to the rubber material C, continue vacuum stirring for 30-45 minutes, and obtain the negative electrode slurry after sieving the material.
[0076] Among them, the weight ratio of each raw material is, negative electrode active material: conductive agent: thickener: dispersant: binder = 93:3.5:1.5:1.5:0.5; the negative electrode active material is lithium titanate, the conductive agent is a mixture of conductive carbon black and carbon nanotubes in a mass ratio of 1:1, the thickener is sodium carboxymethyl cellulose, the binder is styrene-butadiene rubber, the dispersants of experimental groups 15 and 16 are dispersant B and dispersant C respectively, the dispersant of control group 6 is polyvinyl pyrrolidone, the dispersant of control group 7 is triethyl phosphite, and the dispersant of control group 8 is Triton X.
[0077] Take the freshly prepared slurry for testing respectively. After standing for 24 hours, stir the slurry for 1 minute and then test it. Use Lichen ND-10 rotational viscometer and 2# rotor to insert the rotor into the slurry to be tested. The test speed is 100 rpm and the test time is 60 s. Use the multi-point average method to obtain the viscosity value of the slurry. The test results are shown in Table 4.
[0078] Table 4 Slurry viscosity and solid content of experimental group 15-16 and control group 6-8
[0079]
[0080] It can be seen from the data in Table 4 that, compared with other existing dispersants, the solid content of the negative electrode slurry obtained by using the dispersant of the present invention is relatively higher, and the viscosity of the slurry obtained after being placed for 24 hours is significantly lower, which has a significant effect of improving the fluidity of the slurry.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A dispersing aid for lithium-ion battery slurry, having the following structural formula: RO-(CH2CH2O) n (CH2CH2CH2O) m H, where R represents a C2-C8 alkenyl group or a C8-C16 alkylcarbonyl group, n is 10-30, and m is 10-40.
2. The dispersing aid according to claim 1, wherein R represents a C3-C6 alkenyl group or a C8-C16 alkylcarbonyl group, n is 15-25, and m is 20-30.
3. A slurry for lithium-ion batteries, comprising the dispersing aid according to any one of claims 1 to 2.
4. The slurry according to claim 3, characterized in that It also includes an electrode active material and a conductive agent, wherein the electrode active material is a positive electrode active material or a negative electrode active material.
5. The slurry according to claim 4, characterized in that The positive electrode active material is one or more of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, nickel cobalt manganese ternary material, and nickel cobalt aluminum oxide ternary material; the negative electrode active material is graphite, hard carbon, soft carbon, MCMB, graphene, silicon or lithium titanate, and the conductive agent is one of carbon black or carbon nanotubes or a combination of the two.
6. The slurry according to any one of claims 3 to 5, characterized in that: When the slurry is applied to the positive electrode, the slurry further comprises a binder and an organic solvent. When the slurry is applied to the negative electrode, the slurry further comprises a binder, a thickener or water.
7. The slurry according to claim 6, characterized in that When the slurry is applied to the positive electrode, the binder is polyvinylidene fluoride and the organic solvent is N-methylpyrrolidone; when the slurry is applied to the negative electrode, the binder is SBR.
8. A pole piece for a lithium ion battery, characterized in that: The surface of the pole piece is coated with the slurry according to any one of claims 3 to 7.
9. A lithium ion battery comprising the lithium ion battery electrode according to claim 8.
Citation Information
Patent Citations
Lithium ion battery silicon-carbon anode material and preparation method thereof
CN103367727A
Carbon nanotube conductive paste, preparation method thereof and lithium ion battery
CN107706424A
A method for preparing a reinforced polymethacrylimide foam composite material
CN109553905A
Preparation method of waterborne dispersant
CN109666148A
Graphene-coated lithium ion battery ternary positive electrode material
CN110311136A
